2022
DOI: 10.3389/fonc.2021.791411
|View full text |Cite
|
Sign up to set email alerts
|

Combined Association of Tumoral PD-L1 Expression and Pretreatment Presence of Epstein-Barr Virus DNA With Risk Stratification and Prognosis of Patients With Nasopharyngeal Carcinoma

Abstract: BackgroundLittle is known about whether the combination of tumor programmed death-ligand 1 (PD-L1) expression and pretreatment EBV DNA status can help stratify nasopharyngeal carcinoma (NPC) patients by risk of metastasis or predict prognosis.MethodsPD-L1 expression was assessed using immunohistochemical staining of 78 non-keratinizing NPC patients with clinical data. Survival outcomes and independent prognostic factors were identified.ResultsSeventy-eight patients were included, high PD-L1 expression was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(58 reference statements)
1
1
0
Order By: Relevance
“…Therefore, the combination of PD1/PDL1 with other biomarkers such as LAG3 and/or plasma EBV DNA might be clinically significant. This is supported by our study as well as by Li and colleagues, who reported that 93% of patients with detectable pre-treatment plasma EBV DNA and high PDL1 expression were associated with a worse prognosis and multiple studies reporting LAG3 expression to be enriched in dysfunctional T cells in NPC tumors [ 11 , 39 , 46 ]. Myeloid-derived suppressor cells (MDSCs) have been reported to potentially jeopardize the influx and function of T cells and may represent the underlying inducer of these exhausted T cells, which has been reported in RM-NPC patients by Hopkins and colleagues [ 47 ] and is of interest for future studies.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the combination of PD1/PDL1 with other biomarkers such as LAG3 and/or plasma EBV DNA might be clinically significant. This is supported by our study as well as by Li and colleagues, who reported that 93% of patients with detectable pre-treatment plasma EBV DNA and high PDL1 expression were associated with a worse prognosis and multiple studies reporting LAG3 expression to be enriched in dysfunctional T cells in NPC tumors [ 11 , 39 , 46 ]. Myeloid-derived suppressor cells (MDSCs) have been reported to potentially jeopardize the influx and function of T cells and may represent the underlying inducer of these exhausted T cells, which has been reported in RM-NPC patients by Hopkins and colleagues [ 47 ] and is of interest for future studies.…”
Section: Discussionsupporting
confidence: 90%
“…CPS is an index of PD-L1 expression and, like TMB and MSI-H, is used to predict the therapeutic effect of pembrolizumab. Several virus-related cancers, including nasopharyngeal carcinoma (caused by Epstein-Barr virus), oropharyngeal carcinoma (caused by human papillomavirus), and Merkel cell carcinoma (caused by Merkel cell polyomavirus) are considered to arise as a result of PD-L1 expression against a background of chronic inflammation [24][25][26]. Chronic inflammation in response to UV exposure may also increase the CPS in patients with XP.…”
Section: Discussionmentioning
confidence: 99%